EFEITO DOSE-DEPENDENTE DA MALTODEXTRINA NA GLICEMIA E RESPOSTA CARDIOVASCULAR EM DIABÉTICOS TIPO 2 DURANTE EXERCÍCIO AERÓBICO - Thiago Emannuel Medeiros; Luiz Augusto da Silva; João Luiz Lang Pavlak; Carlos Ricardo Maneck Malfatti (Instituto Brasileiro de Pesquisa e Ensino em Fisiologia do Exercício, 2014)
Introduction: The present study investigated the effect of supplementation with different doses of maltodextrin. Before, during and after an exercise protocol with continuous loads predominantly aerobic blood glucose levels and cardiovascular variables in patients with T2DM. Materials and Methods: Six patients diagnosed with T2DM, aged between 40 and 60 years, were supplemented with different doses of carbohydrates (100 mg/kg, 1g/kg e 2g/kg), for 40 minutes of aerobic exercise at 40% heart rate reserve (FCreserve) evaluating cardiorespiratory parameters and blood glucose. We used the ANOVA, and considered significant value than p<0.05. Results: The results show a significant difference in blood glucose for the supplementation of 100 mg/kg of maltodextrin in relation to the group 1 g/Kg (32%, 66 mg/dL; p=0,03) and supplemented with 2g/kg (38%, 79 mg/dL; p=0,02) 40 minutes during the exercise protocol at 40% of FCreserve and 10 minutes after exercise. Discussion: Supplementation with 100 mg/kg maltodextrin can be an effective strategy for preventing rebound hypoglycemia after physical exercise. Conclusion: Control of rebound hypoglycemia with 100 mg/kg of maltodextrin.